2012
DOI: 10.3144/expresspolymlett.2012.102
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of polypyrrole nanofiber and its enhanced electrochemical performances in different electrolytes

Abstract: Abstract.A porous nanocomposite based on polypyrrole (PPy) and sodium alginate (SA) has been synthesized by easy, inexpensive, eco-friendly method. As prepared nanocomposite showed fibrillar morphology in transmission electron microscopic (TEM) analysis. The average diameter of ~100 nm for the nanofibers was observed from scanning electron microscopic (SEM) analysis. As prepared nanofiber, was investigated as an electrode material for supercapacitor application in different aqueous electrolyte solutions. PPy n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…40 For all the electrode materials the broad band around 3425 cm 21 and the band at 2926 cm 21 correspond to the N-H stretching vibration and C-H stretching vibration, respectively. 41…”
Section: Ftir Analysismentioning
confidence: 99%
“…40 For all the electrode materials the broad band around 3425 cm 21 and the band at 2926 cm 21 correspond to the N-H stretching vibration and C-H stretching vibration, respectively. 41…”
Section: Ftir Analysismentioning
confidence: 99%
“…On the other hand, the large molecular chain structure of anionic polyelectrolyte makes it more difficult to be removed from the conducting polymers than the small molecule acid, exhibiting a better stability once being doped in conducting polymers (Nguyen and de Vos 2004). In recent years, several works have demonstrated that using sodium alginate (SA) (Li et al 2011;Sahoo et al 2012), carboxymethylcellulose sodium (CMC) (Basavaraja et al 2012;Chou et al 2011;Peng et al 2012), poly(sodium-4-styrenesulfonate) (PSSNa) , and phosphorylated polyvinyl alcohol (PPVA) (Yang et al 2014) in the preparation process, various nanostructures of conducting polymers could be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…These materials show the capability to store charge Faradically through various charge transfer reactions between electrode and electrolyte, presenting high conductivity in charged state and low equivalent series resistance. The charge/discharge process in these types of pseudocapacitive materials is basically associated with the insertion/deinsertion of counter ions, arising from the electrolyte [66, 67].…”
Section: Resultsmentioning
confidence: 99%
“…In general, more sensitive responses were achieved by CV measurements, but the other electrochemical approaches displayed similar linear concentration ranges of response. It can happens because PPy is a conductive polymer and is considered as a pseudocapacitor where the capacitance developed holds Faradaic origin, with process of chemical/electronic changes as formation/removal of radical cation or radical anion centers, indicating a pseudocapacitance character[66, 67].…”
Section: Resultsmentioning
confidence: 99%